Immunity to rubella: an Italian retrospective cohort study - Francesco Paolo Bianchi; Sara De Nitto; Pasquale Stefanizzi; Angela Maria Vittoria Larocca; Cinzia Annatea Germinario; Silvio Tafuri (BMC, 2019)
Abstract Background International guidelines recommend that healthcare workers (HCWs) have presumptive evidence of immunity to rubella and that susceptible HCWs and doubt cases receive two doses of the MMR vaccine. However, a small percentage of the fully immunized will remain unprotected against wild viruses. Moreover, protective levels of antibodies induced by the vaccine have been shown to decline over time, but a formal recommendation regarding the testing of immunized HCWs for the persistence of IgG against rubella is lacking. Methods The aim of this study was to evaluate the long-term immunogenicity conferred by rubella vaccination and the effectiveness of a strategy for the management of immunized individuals in whom IgG against rubella could not be demonstrated (non-responders). The study enrolled students and medical residents who attended the Hygiene Department of Bari Policlinico University Hospital for biological risk assessment (April 2014 to June 2018). Results Two thousand students and residents with documented immunization (≥2 doses of rubella or MMR vaccine) were tested. In 181 (9%), IgG against rubella was not detectable. The seronegative rate was higher among participants vaccinated at age < 2 years (89.6%) and lower among those immunized at age ≥ 2 years (93.6%; p < 0.0001). The administration of a single MMR booster dose resulted in a seroconversion rate of 98% in the seronegative group. The seroconversion rate after a second booster dose was 100%. No serious adverse events in the re-immunized were recorded. Conclusions An important proportion of individuals immunized for rubella or MMR do not have a protective titer for the disease(s). Our management strategy (booster followed by re-test and, for those who are still negative, a second booster and re-test) is consistent with the goal of achieving immunological memory.